Idiopathic Granulomatous Mastitis - Christina Dilaveri; Amy Degnim; Christine Lee; Daniel DeSimone; Dan Moldoveanu; Karthik Ghosh (Hindawi-Wiley, 2024)
Idiopathic granulomatous mastitis (IGM) is a rare, benign inflammatory disorder of the breast that is often underrecognized. The exact etiology and pathophysiology are unknown, but milk stasis is felt to play a role. Classically, this condition is noninfectious, but many cases are noted to be associated with Corynebacterium species. Most patients affected are parous women with a mean age of 35, and many have breastfed within five years of diagnosis. Patients typically present with a painful mass and symptoms of inflammation, and these features can sometimes mimic breast cancer. Biopsy is needed to make a definitive diagnosis, and noncaseating granulomas are found on core biopsy. Many patients have a waxing and waning course over a period of six months to two years. Goal of treatment is to avoid surgery given poor wound healing, high risk of recurrence, and poor cosmetic outcomes. Medical treatment is preferred and includes observation, antibiotics, steroids, and immune modulators such as methotrexate. In more recent years, topical and intralesional steroids have become the treatment of choice, with similar outcomes to oral steroids.